Method and system development of external target designation with target indication for armoured weapons samples - V. I. Kirnos; A. V. Zubar’; I. V. Kunaev (Омский научный вестник)
When conducting scientific research, the authors solve the problem of implementing a multi-purpose and accurate external target designation in real time, for the targets and critical facilities along the line of sight and beyond it. They achieve minimal dependencies of the external target designation result on the complexity of the target environment, the intensity of the battle, as well as the skills and the training of the crew of the combat vehicle. The peculiarity of this method is the use of a mathematical model of a digital video camera to describe the optical-electronic channels of modern sights of armored weapons.